Prescribing patterns and determinants for elderly patients with Parkinson's disease in Japan: a retrospective observational study using insurance claims databases - Seki, Morinobu; Kawata, Yayoi; Hayashi, Ayako; Arai, Masaki; Fujimoto, Shinji (Frontiers in Neurology, 2023)
Background: This study aimed to determine real-world prescribing patterns and determinants for Japanese patients with Parkinson’s disease (PD), with a focus on patients ≥75 years. Methods: This was a retrospective, observational, longitudinal study of patients with PD (≥30 years, ICD-10: G20 excluding Parkinson syndrome) from three Japanese nationwide healthcare claims databases. Prescription drugs were tabulated using database receipt codes. Changes in treatment patterns were analyzed by network analysis. Factors associated with prescribing patterns and prescription duration were analyzed by multivariable analysis. Results: Of 18 million insured people, 39,731 patients were eligible for inclusion (≥75-year-group: 29,130; <75-year-group: 10,601). PD prevalence was 1.21/100 people ≥75 years. Levodopa was the most commonly prescribed anti-PD drug (Total: 85.4%; ≥75 years: 88.3%). Network analysis of prescribing patterns showed that most elderly patients switched from levodopa monotherapy to adjunct prescription patterns, as did younger patients, but with less complexity. Elderly patients who newly initiated PD treatment remained on levodopa monotherapy longer than younger patients; factors significantly associated with levodopa prescriptions were older age and cognitive impairment. Commonly prescribed adjunct therapies were monoamine oxidase type B inhibitors, non-ergot dopamine agonists, and zonisamide, regardless of age. Droxidopa and amantadine were prescribed as adjunct levodopa therapy slightly more frequently among elderly patients; levodopa adjunct therapy was prescribed when the levodopa dose was 300 mg, regardless of age. Conclusion: Prescribing patterns for patients ≥75 years were levodopa centered and less complex than for those <75 years. Factors significantly associated with levodopa monotherapy and continued use of levodopa were older age and cognitive disorder. Trial Registration: UMIN Clinical Trials Registry (https://www.umin.ac.jp/ctr/index.htm [UMIN000046823])